Private Equity Market Outlook - Anastasia Di Carlo; Roger Kelly (European Investment Fund (EIF), 2010)
This paper presents a general overview of the European Private Equity (PE) market based on industry activity for 2009 published by the European Venture Capital Association (EVCA) in March 2010 and the latest performance data published by Thomson Reuters as of December 2009. The paper is organised in three different sections. An introduction on the global market outlook after the financial crisis is followed by an overview of the main trends currently observed in the European PE market. The analysis focuses on two major dimensions: activity figures (fundraising, investments and divestments) and performance figures (rolling investment horizon). Finally, some future perspectives for the industry conclude the paper. A Private Equity glossary according to EVCA definitions is attached to this paper in Annex 2.
Keywords: 330